Toxic Funding? Conflicts of Interest and their Epistemological Significance. Issue 2 (18th February 2016) - Almassi, Ben
Abstract: Conflict of interest (COI) disclosure has become a routine requirement in communication of scientific information. Its advocates defend COI disclosure as a sensible middle path between the extremes of categorical prohibition on for‐profit research and anything‐goes acceptance of research regardless of origin. To the extent that COI information is meant to aid reviewer and reader evaluation of research, COIs must be epistemologically significant. While some commentators treat COIs as always relevant to research credibility, others liken the demand for disclosure to an ad hominem attack, impugning integrity when better evidence of research credibility is available. Kevin Elliott has argued for clearer justification of COI relevance to research credibility: some interests may be feared to corrupt research results, while others do not, and Elliott provides criteria to discern which financial COIs are actually relevant to research credibility. In this article, I seek to revise and extend Elliott's proposed criteria to COIs more widely. Specifically, I consider the relevance of financial interests as well as nonfinancial advocacy interests to the credibility of research into environmental equity as funded by industry and community groups, with particular attention to criticism and defence of the 1987 United Church of Christ study on the racial demographics of toxic waste facility siting in the United States.